2016
DOI: 10.3390/w8080341
|View full text |Cite
|
Sign up to set email alerts
|

Is Recovery of Large-Bodied Zooplankton after Nutrient Loading Reduction Hampered by Climate Warming? A Long-Term Study of Shallow Hypertrophic Lake Søbygaard, Denmark

Abstract: Nutrient fluctuations and climate warming can synergistically affect trophic dynamics in lakes, resulting in enhanced symptoms of eutrophication, thereby potentially counteracting restoration measures. We performed a long-term study (23 years) of zooplankton in Danish Lake Søbygaard, which is in recovery after nutrient loading reduction, but now faces the effects of climate warming. We hypothesized that the recovery of large-bodied zooplankton after nutrient loading reduction would be hampered by climate warmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…Although a strong decline in TP and phytoplankton biomass is expected to lead to a corresponding decline in zooplankton biomass [13,34], no such response was observed in the S lakes, which corroborates previous observations [35]. Earlier analyses of Danish lakes in recovery from eutrophication have also revealed a weak or insignificant response of zooplankton biomass to re-oligotrophication, suggesting changes also in top-down effects [52,70,71]. Furthermore, a paleolimnological study conducted in Switzerland in three deep lakes covering the past 70-150 years of climate change found that the response of zooplankton to climate change was largely regulated by local changes in nutrient inputs and fisheries [72].…”
Section: Discussionsupporting
confidence: 86%
“…Although a strong decline in TP and phytoplankton biomass is expected to lead to a corresponding decline in zooplankton biomass [13,34], no such response was observed in the S lakes, which corroborates previous observations [35]. Earlier analyses of Danish lakes in recovery from eutrophication have also revealed a weak or insignificant response of zooplankton biomass to re-oligotrophication, suggesting changes also in top-down effects [52,70,71]. Furthermore, a paleolimnological study conducted in Switzerland in three deep lakes covering the past 70-150 years of climate change found that the response of zooplankton to climate change was largely regulated by local changes in nutrient inputs and fisheries [72].…”
Section: Discussionsupporting
confidence: 86%
“…The nutrient loading reduction scenarios projected increased diatom dominance accompanied by an increase in the zooplankton/phytoplankton biomass ratio. As in [15], a higher proportion of small fish and enhanced fish predation with increasing warming were revealed. The simulations generally showed phytoplankton to benefit from a warmer climate and the fraction of cyanobacteria to increase and that a higher external loading reduction is necessary in a future warmer world to maintain the present ecological state.…”
Section: Temperate Climate Zonementioning
confidence: 85%
“…This was shown in an analysis of a comprehensive 23-year long data series from shallow Danish Lake Søbygård, which is in recovery after a major nutrient loading reduction [15]. Focus in this study was on changes in zooplankton.…”
Section: Temperate Climate Zonementioning
confidence: 92%
“…With the increasing proportion of juveniles in the plankti-benthivorous fish population with rising temperatures, higher levels of fish zooplanktivory are to be expected, subsequently resulting in lower zooplankton:phytoplankton biomass ratios [10,67,68] as seen at high nutrient loading in the PCLake simulations. The recent data from the lake has shown an increase in the proportion of small fish, attributed to a higher temperature and a reduction in zooplankton size, but no decline in the zooplankton: chl.-a ratio [7]. Contradicting cross-latitude studies [69,70], the PCLake simulations show total fish biomass to decline with rising temperatures.…”
Section: Effects Of Increasing Temperatures and Reduced Nutrient Loadingmentioning
confidence: 97%
“…Cross-latitude studies have shown fish to play an essential structuring role, in particular in shallow lakes. In a warmer climate, small individuals tend to dominate the fish community and predation pressure on zooplankton increases [6,7]. This results in a lower zooplankton biomass and an increasing proportion of benthi-omnivorous fish and consequently greater resuspension of the sediment [8].…”
Section: Introductionmentioning
confidence: 99%